A systematic review of game-based assessment in education in the past decade - Fan, Su; Zou, Di (Knowledge management & e-learning, 2024)
Educational games, prevalent in contemporary settings, leverage game-based learning (GBL) to actively engage and enhance learners’ knowledge and skill acquisition through captivating in-game learning activities. To assess the effectiveness of GBL, game-based assessment (GBA) has emerged. GBA employs gameplay for learners to attain educational objectives while capturing data for analyzing their in-game competencies. The integration of gameplay in assessments has garnered increasing attention to GBA. This review of 21 studies provides an overview of the application of GBA in the field of education, covering aspects of the publication nature, theoretical frameworks, game types, in-game assessment details, and the assessed subjects and knowledge. Key findings include: (1) the annual number of publications fluctuates; a majority of studies originate from the USA; (2) the supporting theory tends to be unitary, with the evidence-centered design model cited the most; (3) simulation, immersive, and video games with rich game elements are applied most as assessment tools, and in-game assessment details are associated with game features; and (4) GBA is predominantly used in physics education. These findings indicate that applying GBA in education is promising with solid theoretical support, and practitioners are suggested to design GBA according to their educational needs and game features.